Diabetes burden in Brazil: fraction attributable to overweight, obesity, and excess weight - Flor, Luísa Sorio; Campos, Monica Rodrigues; Oliveira, Andreia Ferreira de; Schramm, Joyce Mendes de Andrade (Revista de Saúde Pública, 2015)
OBJECTIVE To estimate the burden of type 2 diabetes mellitus and its percentage attributable to overweight and obesity in Brazil. METHODS The burden of diabetes mellitus was described in terms of disability-adjusted life years, which is the sum of two components: years of life lost and years lived with disability. To calculate the fraction of diabetes mellitus attributable to overweight, obesity, and excess weight, we used the prevalence of these risk factors according to sex and age groups (>; 20 years) obtained from the 2008 Pesquisa Dimensões Sociais das Desigualdades (Social Dimensions of Inequality Survey) and the relative risks derived from the international literature. RESULTS Diabetes mellitus accounted for 5.4% of Brazilian disability-adjusted life years in 2008, with the largest fraction attributed to the morbidity component (years lived with disability). Women exhibited higher values for disability-adjusted life years. In Brazil, 49.2%, 58.3%, and 70.6% of diabetes mellitus in women was attributable to overweight, obesity, and excess weight, respectively. Among men, these percentages were 40.5%, 45.4%, and 60.3%, respectively. Differences were observed with respect to Brazilian regions and age groups. CONCLUSIONS A large fraction of diabetes mellitus was attributable to preventable individual risk factors and, in about six years, the contribution of these factors significant increased, particularly among men. Policies aimed at promoting healthy lifestyle habits, such as a balanced diet and physical activity, can have a significant impact on reducing the burden of diabetes mellitus in Brazil.